Higher Order Generalization of q-Bernstein Operators - Sabancigil, Pembe (Eudoxus Press, Llc, 2010)
We introduce higher order generalization of the q-Bernstein operators. Then we study approximation properties and a Voronovskaja-type theorem for higher order q-Bernstein operators.
Keywords: Convergence; Polynomials